DAKWAH SALAFIYAH: DIALEKTIKA MASYARAKAT BERAGAMA DENGAN PERKEMBANGAN SOSIAL DI INDONESIA - Muchlis Bahar (GoAcademica Research dan Publishing, 2022)
The purpose of this study is to analyze salafiyah da'wah as a dialectic of religious communities with social developments in Indonesia. The research method used in this study is a qualitative method with a descriptive approach. The type of data used in this research is secondary data. This research begins by analyzing the development of various Salafi groups, then analyzing the da'wah methods and the ulama that are used as references, then various criticisms put forward for this group. Based on the results of the analysis and discussion, it can be concluded that the Da'wah of the Salafiyah movement prioritizes informal institutions in building a base. The essence of this movement is the spirit to purify Islamic teachings from cultural understandings that are destructive to Islam itself, which in many ways intersects with certain groups who disagree. In its development in Indonesia, this movement is not repressive towards the government and tends to prioritize various discourses on worship and Fiqh, but attracts many young people because they use social media a lot as a means of Da'wah for the Salafiyah group.